Macana: unidad modular de capacitación y tecnificación de la guadua (2021)
The implementation area of the project is Colombia, in the department of Quindío, municipality of Calarcá; where the intervention is carried out, analyzing the territory and its main characteristics. In the territory, there is a sustainable resource, coming from nature; useful in the field of agribusiness and construction, however, a little-used and undervalued material; The guadua.